9514 1404 393
Answer:
f(x) = -1/2·10^x
Step-by-step explanation:
The y-intercept is -1/2.
The common ratio is (-1/20)/(-1/200) = 10, so the exponential function can be written as ...
f(x) = -1/2·10^x
Answer:
The mathematics of numbers (integers, rational numbers, real numbers, or complex numbers) under the operations of addition, subtraction, multiplication, and division.
Step-by-step explanation:
hope it helps :)
Answer and work down below
Step-by-step explanation:
(x^4)^3=(x^3)^4 , true
=> x^(4×3) = x^(3×4) = x^12
13^4 x 13^7= (13^4)^7, false
13^(4+7) = 13^11
(13^4)^7 = 13^(4×7) = 13^28
y^5 x y^0/y^3=(y^2)^1 , true
y^5 x y^0/y^3 = y^(5+0-3) = y^2
(y^2)^1 = y^(2×1) = y^2
q^0 x q^5/q^2=(q^3)^2/q^3, true
q^0 x q^5/q^2= q^(0+5-2)= q^3
(q^3)^2/q^3 = q^(3×2-3) = q^3
Answer:
y = x + 1
Step-by-step explanation:
The gradient of a line can be defined by the equation:
m (gradient) = (y1 – y2 ) ÷ (x1 – x2) ----> "1" and "2" should be in subscript
For (-7,-6) we use x2 and y2 (because this point can be anywhere along a line):
x2 = -7, y2 = -6
Plug these values into the formula above:
m = (y-(-6)) ÷ (x-(-7))
m = (y+6) ÷ (x+7)
At this stage, the equation can't be solved as there are two unknowns. Therefore, the gradient must be found another way. Two lines are parallel if they have the same gradient - in their y=mx+c equations, m will be equal.
x - y=7 is the line alluded to in the question. Rearranging this equation into the line equation format gives:
y = x-7 ---> The gradient (coefficient of x) is 1.
Therefore, the gradient of the other parallel line must also be 1.
This can be substituted into the previous equation to give:
1 = (y+6)÷(x+7)
x+7 = y+6
x+1 = y
Therefore, the answer is y=x+1